THE EFFECT OF A COMBINATION OF FOOT MASSAGE THERAPY AND DRIED ROSELLE FLOWER TEA ON REDUCING BLOOD PRESSURE IN HYPERTENSION IN SERANG HAMLET, MEKARJAYA VILLAGE, PURWASARI DISTRICT, KARAWANG REGENCY - Desty Lismayanti; Sarini, Sarini; Yanti Rosmayanti; Sumitro, Sumitro; Okti Rahayu Asih; Nining Sugihartati; Jumaedi, Jumaedi; Iin Ira Kartika (International Journal of Social Science, 2023)
Hypertension is blood pressure that increases beyond the normal limit, namely above 140 mmHg and/or diastolic blood pressure of 90 mmHg. Hypertension in the elderly aged >50 years if they have hypertension with a systolic value >140 mmHg. Mekarjaya Village has 58% of hypertension cases and is the largest number of PTM cases in the elderly in Mekarjaya Village. This research was carried out in the Serang hamlet, Mekarjaya Village, the working area of ​​the Purwasari Community Health Center. The research was carried out by providing a combination of foot massage therapy and drinking tea brewed with dried rosella flowers. Foot massage therapy and roselle flowers are known to help reduce blood flow because blood flow becomes smooth and roselle has been proven to help reduce the amount of fatty plaque that sticks to blood vessels. The aim of the research was to determine the effect of a combination of foot massage therapy and drinking roselle tea on reducing blood pressure in hypertensive patients. This research method uses a quantitative method with a quasi-experimental pretest-posttest design with control group design. The sample used was 48 people, of which 24 people were in the intervention group and 24 people were in the control group. The analysis used in this research is the Wilcoxon Sign Rank test. The research results showed that there was an effect of a combination of foot massage therapy and drinking tea steeped in dried roselle flowers on changes in blood pressure in elderly hypertensive patients at the Posyandu for the elderly in Serang hamlet, Mekarjaya Village, Purwasari District with a p-value (0.000). Conclusion: The combination intervention of foot massage and roselle flower tea is effective to help reduce blood pressure in patients with hypertension